Validation and diagnostic accuracy of coin rotation task for manual dexterity and coordination in children with specific learning disorder. Issue 10 (8th May 2022) - Meimandi, Mahsa; Azad, Akram; Taghizadeh, Ghorban; Mohammadi, Parvaneh
Abstract: Background: This study aimed at determining validity, reliability, and diagnostic accuracy of Coin Rotation Task (CRT) in assessing manual dexterity and coordination of children with specific learning disorder (SLD). Methods: In this non-experimental cross-sectional study, 120 children (typically developing children = 60, children with SLD = 60, mean age ± SD =9.18 ± 0.55) were recruited. Test–retest reliability and construct validity of CRT were assessed. Multivariate regression analysis was performed on CRT scores by considering age and gender as covariates and children with SLD with mild dexterity impairment and severe dexterity impairment (SDI) as outcome variables. Receiver-operating characteristics (ROC) curve analysis was carried out to derive validity parameters. Results: Test-retest reliability of the CRT scores in both subtests were excellent in children with SLD (ICC2, 1 : 0.93–0.95) and good to excellent in typically developing children (ICC2, 1 : 0.72–0.82). Acceptable construct validity of CRT was also found. The CRT cut-off points were 23 (sensitivity= 89.29%, specificity= 70.37%) and 28 (sensitivity= 80.33%, specificity= 86.36%) for discriminating children with SLD and SDI from typically developing children in dominant and non-dominant hand, respectively. Conclusions: The present study indicated good to excellent test-retest reliability, acceptable validity, and high diagnostic accuracy for diagnosing children with SLD based on their dexterity impairment level. Implications for Rehabilitation: The Coin Rotation Task (CRT) was modified and validated for use in children. The CRT is a reliable and valid tool with high diagnostic accuracy. The CRT has a good ability for discriminating children with specific learning disorder with severe dexterity impairment form typically developing children. Treatment plans and research designs can be performed by using this valid, reliable, and easy to administer tool.